2004
DOI: 10.1094/cchem.2004.81.3.392
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Retrogradation Properties of Rice Starches with Amylose Content and Molecular Properties

Abstract: The increases in storage modulus (G′), retrogradation enthalpy change (ΔH) and ΔH‐related Avrami kinetic parameters of gelatinized rice starch dispersions at 25% (w/w) were investigated with respect to storage period, amylose content (AC), and molecular properties. Three high‐AC and five low‐AC rice cultivars were compared for understanding the multiple influences of AC and molecular properties involved. After refining the results of correlation analysis, the G′ of just‐cooled samples changed positively, mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…The relationship between the rheological properties of rice starch gels and starch characteristics has been reported in other studies;Takahashi and Fujita (2017) showed using mutant rice varieties that the dynamic viscoelasticity of rice starch gels was strongly affected by the amylose content and the amount of amylopectin short chains Lii, Lai, and Shen (2004). The relationship between the rheological properties of rice starch gels and starch characteristics has been reported in other studies;Takahashi and Fujita (2017) showed using mutant rice varieties that the dynamic viscoelasticity of rice starch gels was strongly affected by the amylose content and the amount of amylopectin short chains Lii, Lai, and Shen (2004).…”
supporting
confidence: 58%
“…The relationship between the rheological properties of rice starch gels and starch characteristics has been reported in other studies;Takahashi and Fujita (2017) showed using mutant rice varieties that the dynamic viscoelasticity of rice starch gels was strongly affected by the amylose content and the amount of amylopectin short chains Lii, Lai, and Shen (2004). The relationship between the rheological properties of rice starch gels and starch characteristics has been reported in other studies;Takahashi and Fujita (2017) showed using mutant rice varieties that the dynamic viscoelasticity of rice starch gels was strongly affected by the amylose content and the amount of amylopectin short chains Lii, Lai, and Shen (2004).…”
supporting
confidence: 58%
“…By including the results in this study and some data reported elsewhere [8,[37][38][39][40], the CL, ECL, and ICL for Dioscorea spp. amylopectins found so far are [19][20][21][22][23][24][25][26][27][28][29][11][12][13][14][15][16][17][18][19], and 4-11 AGU, respectively, and generally higher than those of rice amylopectins (15)(16)(17)(18)(19)(20)(21)(22)(11)(12)(13)(14)(15)(16), and 3-6 AGU, respectively) [19][20]24]. The b-amylolysis limits for Dioscorea amylopectins are 51-67%, close to those for rice amylopectins (56-62%) [19,20,24] and many tuber and root amylopectins (56-59%) [38].…”
Section: Comparison Of Amylopectin Structure and Physical Properties mentioning
confidence: 99%
“…It is known that the molecular properties of starch components (especially amylopectin chain lengths) strongly influence the gelatinization temperature, pasting behavior [13][14][15][16], retrogradation and rheological properties [17][18][19][20] of starch dispersions, and the eating quality and storage stability of starchy products like cooked rice [20][21]. Their influences apparently correlate with amylose con-tent [15,22] and very possibly with monophosphate ester content noticeable in yam starch [15,23]. Nonetheless, how these parameters interactively affect the physical property of yam starches is still not understood.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is mainly associated with the cooling rate of the flake after addition of temperature, in which grains maintained at high temperatures for a long period of time, can have this process dramatically accelerated. In addition, the retrogradation is associated with the storage condition (high temperature and humidity) (JOUPPILA; ROOS, 1997) and the amylose content (LII; LAI;SHEN, 2004). Thus, grains with starch granules with higher amylose content are more susceptible to this retrogradation process than those with low amylose content.…”
Section: Starch Digestion and Corn Processingmentioning
confidence: 99%
“…Moreover, after gelatinization with steam-flaking, gelatinized starch can undergo to retrogradation, which is the reassociation of starch molecules e and formation of tight bound structures stabilized by hydrogen bonds, in which starch resists to amylase digestion. This process is associated with the delay in the cooling rate of the flake after addition of temperature, to high temperature and humidity (JOUPPILA; ROOS, 1997) and to greater amylose content (LII;LAI;SHEN, 2004) which is the case of Brazilian corn types.…”
Section: Intake Performance and Carcass Traitsmentioning
confidence: 99%